Determinants of financial distress in the building construction sub-sector companies listed on the Indonesia Stock Exchange - Sekar Setowening; Djuminah Djuminah (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This study aims to analyze the influence of profitability, leverage, and intellectual capital on financial distress in companies within the building construction sub-sector.Method — The research method involves quantitative and regression analysis. The sample consists of companies within the building construction sub-sector that consistently published financial reports during the period 2016-2021. The research population comprises 96 building construction companies listed on the Indonesia Stock Exchange, with 16 companies meeting the sample requirements. Data collection is performed using purposive sampling, and the analysis is conducted using EViews 10. Various tests, including classic assumption tests, feasibility analysis models, panel regression analysis, and coefficient of determination tests, are employed in the analysis.Result — The study results indicate a significant positive effect of profitability on the level of financial distress, suggesting that higher levels of profitability correspond to lower financial distress. Conversely, leverage demonstrates a significant negative effect on financial distress, implying that higher levels of leverage are associated with increased financial distress for the company. However, the study did not identify a significant relationship between intellectual capital and the level of financial distress, suggesting that the level of intellectual capital does not significantly influence the level of financial distress.Practical implications — Management in the building construction sub-sector is encouraged to prioritize strategies and tactics aimed at enhancing company profitability. Focusing on efforts to improve operational efficiency, optimize asset utilization, and enhance the effectiveness of marketing strategies can contribute to an increase in the company's profitability.